The ANALISIS RESPON SEGMEN PSIKOGRAFIS TERHADAP PASAR KAGET DI KOTA BATAM: Segmen Psikografis - Tiurniari Purba (JURNAL AKUNTANSI BARELANG, 2018)
Abstract This study aims to determine consumer response based psychografic segment and to the shock markets in Batam City, especially in the nine districts that are in the geographic area of Batam Island. To analyze the response of segments to the shock market used qualitative method with descriptive approach. Analysis method is Interpretative Phenomenologi Analysis (IPA). Using Model Analysis Spradley with departing from the broad focus of study and then find more widespread. Batam city composed of 12 districts, there are only nine districts have 27 shock markets. In this study, geographic units based on those districts. Spreading shock market dominated by the District of Batu Aji with 10 shock market following the District of Sekupang with five shock market, while the District Sagulung four shock market and the District of Batam Kota have two shock market. For Nongsa District, Batu Ampar, Bengkong, Sei Beduk, Lubuk Baja, each one shock market. All the time, social class, personality, and lifestyle are different always change and provide opportunities for industrial goods and services. The same thing happened with the shock market business. In Batam, for the nine districts that consist of different characteristics of the variable social class, personality, and lifestyle, mingling in the shock market. There is no limit to the specific psychographic segments in the shock market in Batam City. Key words: Segment, Psychographic, Shock Market